ASSESSING THE KNOWLEDGE AMONG NURSES REGARDING NOSOCOMIAL/HEALTHCARE ASSOCIATED INFECTIONS - IQBAL, AJMAL; ABBAS, FAKHAR (International Journal of Allied Health Sciences, 2021)
Background: Healthcare associated infection (HAI) or nosocomial infection or hospital acquired infection is an infection that develops in the patients during their stay in the hospital/healthcare facility that may prolong their length of stay in the hospital. Healthcare associated infections affect the morbidity and mortality rates significantly. The study aimed to assess the knowledge of nurses regarding nosocomial infection. Materials and Methods: A descriptive study design was used and data was collected from two hospitals of Lahore (provincial capital) and Islamabad (federal capital) between August 2014 to November 2014. A questionnaire was used to interview the participants (nurses). Result: The total number of 80 nurses having different levels of qualification, experience and designation were interviewed. Five nurses out of 80 (6.25%) were found to have poor knowledge regarding HAIs, 47 (59%) nurses had average knowledge and 28 (35%) nurses had excellent knowledge about the HAIs. Conclusion: Based on the results, it can be concluded that there is a need for continuous education in the discipline of infection control for nurses to keep their knowledge updated. Nurses’ practice in different measures of infection control must be monitored and interventions should be devised when required. Keywords: Nosocomial, healthcare, infections, knowledge, interventions